Chloride channels in stroke - Zhang Ya-ping; Zhang Hao; Duan Dayue Darrel (Acta Pharmacologica Sinica, 2016)
Ya-ping ZHANG1, 3, Hao ZHANG2, *, Dayue Darrel DUAN3, * 1The Department of Cardiology, the Third Xiang-Ya Hospital of Central South University, Changsha 450013, China; 2The Surgery Department, Huashan Hospital, Fudan University, Shanghai 200040, China; 3The Laboratory of Cardiovascular Phenomics, the Department of Pharmacology, University of Nevada School of Medicine, Reno, Nevada 89557, USA Vascular remodeling of cerebral arterioles, including proliferation, migration, and apoptosis of vascular smooth muscle cells (VSMCs), is the major cause of changes in the cross-sectional area and diameter of the arteries and sudden interruption of blood flow or hemorrhage in the brain, ie, stroke. Accumulating evidence strongly supports an important role for chloride (Cl–) channels in vascular remodeling and stroke. At least three Cl– channel genes are expressed in VSMCs: 1) the TMEM16A (or Ano1), which may encode the calcium-activated Cl– channels (CACCs); 2) the CLC-3 Cl– channel and Cl–/H+ antiporter, which is closely related to the volume-regulated Cl- channels (VRCCs); and 3) the cystic fibrosis transmembrane conductance regulator (CFTR), which encodes the PKA- and PKC-activated Cl– channels. Activation of the CACCs by agonist-induced increase in intracellular Ca2+ causes membrane depolarization, vasoconstriction, and inhibition of VSMC proliferation. Activation of VRCCs by cell volume increase or membrane stretch promotes the production of reactive oxygen species, induces proliferation and inhibits apoptosis of VSMCs. Activation of CFTR inhibits oxidative stress and may prevent the development of hypertension. In addition, Cl– current mediated by gamma-aminobutyric acid (GABA) receptor has also been implicated a role in ischemic neuron death. This review focuses on the functional roles of Cl– channels in the development of stroke and provides a perspective on the future directions for research and the potential to develop Cl– channels as new targets for the prevention and treatment of stroke. Keywords: chloride channel; stroke; hypertension; vascular remodeling; oxidative stress Dayue Darrel DUAN is supported by the NIH grant #HL106256 and AHA Western State Affiliate Grant-in-Aid #11GRNT7610161. Ya-ping ZHANG is supported by the National High Technology Research and Development Program of China #2009AA022703 and National Science and Technology Major Projects for “Major New Drugs Innovation and Development” #2009ZX09501-032. * To whom correspondence should be addressed. E-mail dduan@medicine.nevada.edu (Dayue Darrel DUAN); drhao@hotmail.com (Hao ZHANG) Received 2012-08-19 Accepted 2012-09-06